2020
DOI: 10.2147/opth.s271858
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Performance and Safety of the Extended Depth of Focus Implantable Collamer<sup>®</sup> Lens (EDOF ICL) in Phakic Subjects with Presbyopia</p>

Abstract: Purpose To evaluate the performance and safety of the Extended Depth of Focus Implantable Collamer ® Lens (EDOF ICL) for improvement of uncorrected near, intermediate and distance visual acuity in phakic subjects with myopia and presbyopia. Design Prospective multicenter study. Methods Presbyopic subjects who required an EDOF ICL in the range of −0.50 D to −18.00 D, exhibited ≤ 0.75 D refractive astigmatism and requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Calculating ICL size is essential for the success of the surgery, as miscalculations can lead to complications such as cataract, angular closure, etc. According to the results reported by Parker (Packer, Alfonso et al 2020) in his work, there is still no definitive method for determining the size of the ICL, which is why it is considered necessary to analyse the current formulas available and compare them with clinical outcomes. In another literature review recently published, Montés-Micó et al concluded that anterior segment anatomy should be carefully studied to obtain good results and avoid complications (Ando, Kamiya et al 2020, Montés-Micó, Ruiz-Mesa et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Calculating ICL size is essential for the success of the surgery, as miscalculations can lead to complications such as cataract, angular closure, etc. According to the results reported by Parker (Packer, Alfonso et al 2020) in his work, there is still no definitive method for determining the size of the ICL, which is why it is considered necessary to analyse the current formulas available and compare them with clinical outcomes. In another literature review recently published, Montés-Micó et al concluded that anterior segment anatomy should be carefully studied to obtain good results and avoid complications (Ando, Kamiya et al 2020, Montés-Micó, Ruiz-Mesa et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, special formulas for post-laser refractive surgery such as those included in the ASCRS online calculator ( accessed on 16 March 2023), thick-lens or ray-tracing formulas should be used [ 33 , 34 ]. Presbyopic phakic IOLs could also be an alternative for those patients, but CSDC studies are still required to determine if CS is also maintained along the whole defocus range [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A surgical correction of presbyopia may consist of a cornea surgery (using excimer and femtosecond laser procedures for creating monovision or multifocality, intrastromal radial segments, or corneal inlays) or intraocular lens (IOL) implantation (both with pseudophakic IOLs or, more recently, with phakic IOLs). [1][2][3][4] The pseudophakic correction of presbyopia consists of implantation of various IOLs after the patient's crystalline lens extraction (either clear lens extraction or cataract surgery). There are a rapidly growing number of pseudophakic IOLs available on the market, which are broadly categorized as "standard monofocal," multifocal diffractive, multifocal refractive, and extended depth of focus IOLs.…”
Section: Conclusion: Pseudophakic Mini-monovision In Hyperopicmentioning
confidence: 99%